Compassion without compromise : how the gospel frees us to love our gay friends without losing the truth - Barr, Adam T. (Minneapolis, Minnesota : Bethany House Publishers, 2014)
"Two pastors offer compassionate, biblical answers about homosexuality and practical, real world advice on how to think and talk about this controversial issue with loved ones"--
Includes bibliographical references.
Keywords: Church work with gay people; Love -- Religious aspects -- Christianity; Church work; Homosexuality -- Religious aspects -- Christianity; Sex -- Religious aspects -- Christianity; Church work; Church work with gays; Homosexuality -- Religious aspects -- Christianity; Love -- Religious aspects -- Christianity; Sex -- Religious aspects -- Christianity